On the origin of internal obstacles to dislocation glide in single-phase NiFe random alloys. (1st January 2022) - Osetsky, Yuri; Morris, James
Abstract: Over the past decade, a new class of unconventional alloys, where several constitutive elements are presented in close to equal concentrations, is considered as promising structural materials in many applications. Properties and behavior of many concentrated solid solution alloys (CSSAs) under different conditions, including mechanical loading, differs from that of conventional alloys and has been the subject of intensive studies by different techniques. A key feature of these materials is that there is no clear distinction between solute and solvent species of atoms, which is the conventional approach to considering dislocation motion in alloys. To understand this regime, we have recently reported on the glide of a screw dislocation glide in a simple equiatomic NiFe alloy and reported the two-mode character. At low applied stress, the dislocation motion is similar to a glide through a field of obstacles. In this paper, we report the results of a detailed study on the nature of these internal obstacles. We demonstrate that these are not conventional localized "obstacles" but is the result of significantly different energies of instantaneous dislocation configurations over the alloy bulk. The strong pinning positions are associated with composition changes in the partial dislocation cores, while observing no significant composition changes along the stacking faults. Local energies can vary significantly, as demonstrated using simulations of short-periodicity dislocation lines. Therefore, the critical stress to move a dislocation under such conditions is not a constant Peierls stress but represents a wide spectrum of barriers between different non-straight valleys that the dislocation line accommodates in the bulk at particular stress/strain conditions. Graphical abstract: Image, graphical abstract